ENHANCING ENGLISH LANGUAGE PROFICIENCY FOR STUDENTS OF DIPLOMACY: EFFECTIVE TEACHING APPROACHES: Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This article explores various methodologies for teaching English to students pursuing studies in diplomacy. With the increasing importance of English as a global lingua franca in diplomatic circles, it is imperative to equip future diplomats with proficient language skills. The study reviews existing literature, evaluates different teaching methods, and presents analysis and results to determine effective approaches. The findings aim to inform educators and policymakers in designing language programs tailored to the specific needs of diplomatic studies.